Augmented Reality Objek Wisata Bogor Menggunakan Algoritma Lucas Kanade Dengan Metode Marker Based Tracking - Fikry Ali Sya’ Dani; M Iwan Wahyuddin; Winarsih Winarsih (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Information technology today, is very developed and easy to find. Especially in information on Bogor tourist attractions such as the Bogor Palace, Tugu Kujang, and Pakansari Stadium. However, the data information held is not completely valid. Because many tourists get data that is not suitable, due to the lack of information obtained. Therefore, the researchers tried to make an android-based "Tourism Object in Bogor" application using Augmented Reality (AR) technology and the Lucas Kanade Algorithm, as well as Marker Based Tracking efforts to make it easier to get the information desired by tourism. Bogor is one of the cities in West Java Province that attracts many tourists, especially domestic tourists. However, there are still many tourist attractions in Bogor that are still many tourist attractions that have not been visited and are still not widely known by tourists. Until now, researchers have tried to make an android-based "Tourism Object in Bogor" application so that tourists know the shape of objects and information such as the Bogor Palace, Tugu Kujang, and Pakansari Stadium. Using Augmented Reality (AR) technology, the technology itself has photos, sounds, and 3d objects that can bring virtual 3d objects into the real world. The "Tourism Object in Bogor" application uses Android Studio, Unity, Sketchup, Vuforia, and Visual Studio. In order to make it easier for tourists to identify data on tourist attractions they want to visit. The application "Tourism Objects in Bogor" serves to share data information for local and foreign tourists, because this is an opportunity for the Bogor Regional Government to improve services and facilities in Bogor, so that tourists feel safe arriving and visiting Bogor.